Managing Diversity in the Workplace: Analysing the investment banking sector on promoting equal opportunities regarding sexual orientation in the UK - Yamahaki, Camila (2007)
Although there are 3.6 million gay people in Britain and 1.7 million lesbian, gay and bisexual people in Britain's workforce (Stonewall 2006a), dealing explicitly with issues of sexual orientation is still a taboo topic (Stonewall 2004b). Research has shown that LGB people who are out at work are vulnerable to harassment, bullying and discrimination in their careers (Stonewall 2004b). According to 2007 Stonewall Workplace Equality Index, the investment banks are the leaders in promoting equal opportunities for the LGB people in the UK. In order to analyse such sector, this dissertation has assessed the motivations of the top six investment banks, according to Stonewall Index, in promoting equal opportunities in terms of sexual orientation as well as the perception of the LGB employees in relation to the banks' policies. It concludes that the main motivations relates to market factors regarding attraction and retention of potential and current clients and employees. Also, the LGB agenda in these banks is being pushed by the LGBT Interbank Forum, an organization which was created by a number of investment banks to, among other goals, share best practices. As for the perception of the employees in relation to the banks'policies and practices, they are overall positive.